Guinness world records 2020 - Glenday, Craig; Guinness World Records Limited ([London, England] Guinness World Records, 2019)
An updated edition of the compendium of records includes entries ranging from athletic achievements and cutting-edge cyborg innovations to social-media stars and boundary-breaking art.
Cover title.
Includes index.
6.0
9-12
Keywords: World records; Curiosities and wonders; World records; Curiosities and wonders